Alcohol and Drug Use as Predictors of Intentional Injuries in Two Emergency Departments in British Columbia1. (15th February 2013) - Cherpitel, Cheryl J.; Martin, Gina; Macdonald, Scott; Brubacher, Jeffrey R.; Stenstrom, Rob
<x xml:space="preserve">Abstract</x> Background While a substantial literature exists demonstrating a strong association of alcohol and intentional injury, less is known about the association of intentional injury with recreational drug use, either alone, or in combination with alcohol. Objectives The risk of intentional injury due to alcohol and other drug use prior to injury is analyzed in a sample of emergency department (ED) patients. Methods Logistic regression was used to examine the predictive value of alcohol and drug use on intentional versus non‐intentional injury in a probability sample of ED patients in Vancouver, BC (n = 436). Results Those reporting only alcohol use were close to four times more likely (OR = 3.73) to report an intentional injury, and those reporting alcohol combined with other drug(s) almost 18 times more likely (OR = 17.75) than those reporting no substance use. Those reporting both alcohol and drug use reported drinking significantly more alcohol (15.7 drinks) than those reporting alcohol use alone (5 drinks). Conclusions These data suggest that alcohol in combination with other drugs may be more strongly associated with intentional injury than alcohol alone. Conclusions and Scientific Significance The strong association of alcohol combined with other drug use on injury may be due to the increased amount of alcohol consumed by those using both substances, and is an area requiring more research with larger samples of intentional injury patients. (Am J Addict 2013;22:87‐92)